ETNOBOTANI PEMANFAATAN TUMBUHAN BERACUN DI DESA KERANJI PAIDANG KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Irtiawati, Irtiawati; Rafdinal, Rafdinal; Wardoyo, Elvi Rusmiyanto Pancaning (Universitas Tanjungpura, 2020)
Poisonous plants are defined as plants that contain chemical compounds that are toxic and can cause tissue or organ damage, and can even cause the death of other organisms. The people of Keranji Paidang have used poisonous plants to repel pests and poison fish. The purpose of this study was to determine the types of poisonous plants and plant parts used as poison. This research was conducted in Keranji Paidang Village, Sengah Temila District, Landak Regency. This study used a snowball sampling method with 12 respondents consisting of the village head, adat leaders, hamlet heads, and other community members who have knowledge of poisonous plants. The results obtained 25 plant species from 20 families and 25 genera. The most widely used families are Fabaceae (3 species), Euphorbiaceae (2 species), Sapindaceae (2 species) and Solanaceae (2 species). The most widely used part of the plant was the leaves (48.39%). The most widely used methods of processing and using poisonous plants were pounding (38.10%) and spraying (51.85%).